2019
DOI: 10.1097/mpg.0000000000002194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Approach to Nonalcoholic Fatty Liver Disease by Pediatric Gastroenterologists in the United States

Abstract: Objectives: Nonalcoholic fatty liver disease (NAFLD) is common; however, no information is available on how pediatric gastroenterologists in the United States manage NAFLD. Therefore, study objectives were to understand how pediatric gastroenterologists in the US approach the management of NAFLD, and to identify barriers to care for children with NAFLD. Methods: We performed structured one-on-one interviews to ascertain each individual pediatric gastroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Although screening is recommended for hypertension, dyslipidemia, and type 2 diabetes in children with NAFLD, Shapiro et al found that only half (47.5%) of paediatric gastroenterologists screened for these comorbidities. 27 Notably, time constraints were associated with poor screening. Providers who spent more than 25 min at the initial visit were more likely to screen, illustrating the need for sufficient time to address comorbidities in children with NAFLD.…”
Section: Comorbid Conditions Associated With Nafldmentioning
confidence: 99%
“…Although screening is recommended for hypertension, dyslipidemia, and type 2 diabetes in children with NAFLD, Shapiro et al found that only half (47.5%) of paediatric gastroenterologists screened for these comorbidities. 27 Notably, time constraints were associated with poor screening. Providers who spent more than 25 min at the initial visit were more likely to screen, illustrating the need for sufficient time to address comorbidities in children with NAFLD.…”
Section: Comorbid Conditions Associated With Nafldmentioning
confidence: 99%
“…However, despite these recommendations, only approximately half of paediatric gastroenterologists screen for those comorbidities. 86 Acknowledgement and evaluation of NAFLD comorbidities is an essential tool that will reduce the impact of severe outcomes in young adults and is an important consideration for next-generation, whole child treatment regimens.…”
Section: Comorb Id Itie S In Children With Nafldmentioning
confidence: 99%
“…Thus, it is not surprising that, aligning with the evidence outlined above, the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) suggests screening for comorbidities such as T2DM, hypertension and dyslipidemia in children with NAFLD, 85 and this list of comorbidities may increase in the future as more evidence is generated. However, despite these recommendations, only approximately half of paediatric gastroenterologists screen for those comorbidities 86 . Acknowledgement and evaluation of NAFLD comorbidities is an essential tool that will reduce the impact of severe outcomes in young adults and is an important consideration for next‐generation, whole child treatment regimens.…”
Section: Comorbidities In Children With Nafldmentioning
confidence: 99%
“…These data suggest that there is a role for vitamin E in the treatment of NAFLD but that only a subset of patients respond. Despite this, according to a recent nationwide survey of US pediatric gastroenterologists (72% response rate), 51% reported using medications to treat NAFLD, and the most commonly used medication was vitamin E . Therefore, studies are needed to determine the characteristics of patients, who are more likely to respond to this intervention.…”
Section: Introductionmentioning
confidence: 99%